THE EFFECT OF SENSITIVE INTERVENTIONS ON STUNTING REDUCTION EFFORTS - Uswatun Khasanah; Esyuananik Esyuananik; Anis Nur Laili; Nurlailis Saadah (Universitas Airlangga, 2022)
Background: Stunting occurs when a toddler's growth is not age-appropriate, characterized by a child's body length or height being less than age-appropriate. Reducing stunting requires integrated interventions, including both nutrition-specific and nutrition-sensitive interventions. Efforts to address the indirect causes of stunting are summarised in nutrition-sensitive interventions, which account for 70% of stunting interventions. Purpose: This study aims to analyze the effect of sensitive interventions on efforts to reduce stunting among children under five years of age at Puskesmas (Community Health Centre) in Bangkalan Regency. Methods: The study was conducted in March-September 2020 with an analytical cross-sectional design. The population in this study were all children aged 1 to 5 years who were in the working area of Bangkalan District in January - December 2019, totaling 430. A sample of 207 was taken by random cluster sampling. The independent variables in this study were clean and healthy living behaviour (PHBS), access to family planning services, and insurance ownership (only BPJS because this insurance is the most commonly owned by the community). In comparison, the independent variable was stunting in toddlers. The data used were primary and secondary data using closed question questionnaires, Maternal and Child Health books, and cohorts of pregnant women/toddlers. Data were analyzed using logistic regression. Results: It was found that sensitive interventions that affect the incidence of stunting were PHBS with a p-value = 0.03 and BPJS ownership variables with a p-value = 0.04, which means that PHBS and BPJS affect the incidence of stunting in children under five. Meanwhile, the variable access to family planning does not affect stunting. Conclusion: Sensitive interventions affecting stunting incidence are PHBS and BPJS ownership.